Strategi Membangun Potensi Spiritual Dan Memelihara Energi Intelektual Siswi SMA Al Falah Kadur Pamekasan Melalui Peringatan Isra' Mi'raj Rasulullah SAW - Zakki, Mohammad (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The service packaged in seminars was carried out by the Al Faalah High School Intra-School Organization (OSIS) and the Management of the Nahdlatul Ulama Women's Student Association Commissariat (PKP IPPNU) Kadur Pamekasan District. This dedication contains about the Isra' Mi'ra' of the Prophet Muhammad. to provide new guidance, direction, inspiration and motivation to all female students so they can emulate the life of the Prophet. This event is a historical moment to explore spiritual potential and maintain intellectual awareness. The seminar activities were attended by high school students. Al Falah Class XII, Representatives of Classes X and The aim of holding this seminar is: 1) Reminiscing and renewing female students' memories about the historical momentum that occurred during Isra' Mi'ra', 2) Understanding and inspiring female students to have awareness in increasing spiritual and intellectual values ​​through the Isra' Mi'raj journey, 3 ) Facilitate female students and all audiences in exchanging ideas, insights and experiences by referring to the events of Isra' Mi'ra'. The results of the seminar service are: 1) Prayer as one of the main missions of Isra' Mi'raj, with solemn prayer it can be a family education in bringing peace and clarity of soul, 2) Motivating female students to be diligent in building spiritual and intellectual potential to the fullest. appreciate and understand the story of the Prophet's life journey, especially during the Isra' Mi'raj, 3) Building the soul's potential in facing trials or tests in a student's life through interpreting the meaning of the Prophet's tests during the Isra' Mi'raj journey.